Antibody against immunoglobulin E contained in blood components as causative factor for anaphylactic transfusion reactions. Issue 8 (3rd March 2014) - Abe, Takaaki; Shimada, Eiko; Takanashi, Minoko; Takamura, Takeshi; Motoji, Kyosuke; Okazaki, Hitoshi; Satake, Masahiro; Tadokoro, Kenji
<x xml:space="preserve">Abstract</x> Background Determining the mechanism underlying the development of transfusion reactions is important in transfusion therapy. Two bags of fresh‐frozen plasma obtained from a donor (index donor) were implicated in two cases of anaphylactic transfusion reactions. Study Design and Methods The serum prepared from the index donor plasma transfused into the second patient (Patient 2) was evaluated using cord blood–derived mast cells (CBMCs) incubated with Patient 2 plasma. The component in the serum required for the degranulation was determined and quantified by chromatography in combination with degranulation assay, Western blot analysis, and enzyme‐linked immunosorbent assay. The component in the plasma required for CBMC sensitization was determined using human immunoglobulin (Ig)E or normal plasma in place of Patient 2 plasma in the assay. Sera collected from the index donor between 2001 and 2008 were examined for the CBMC degranulation factor. Results The donor serum activated CBMCs incubated with Patient 2 plasma. The IgG fraction of the donor serum induced degranulation of CBMCs sensitized with IgE or plasma containing a normal IgE concentration. The IgG anti‐IgE at a concentration higher than 2200 ng/mL, which showed CBMC degranulation activity, was detected in the donor sera for at least 7 years. Conclusion Transfusion of a high concentration of the anti‐IgE in the donor plasma was suggested to induce mast cell degranulation in the patients leading to the development of anaphylactic transfusion reactions. Antibodies existing in not only the patient circulation but also the transfused blood might cause transfusion‐induced anaphylaxis.